Acknowledgment to the Reviewers of ChemEngineering in 2022 - ChemEngineering Editorial Office, ChemEngineering Editorial Office (ChemEngineering, 2023)
High-quality academic publishing is built on rigorous peer review. [...]of whether the articles they examined were ultimately published, the editors would like to express their appreciation and thank the following reviewers for the time and dedication that they have shown ChemEngineering: Abdulgalim Isaev Luguang Wang Agata Małysiak Luis F. Bobadilla Ahmed K. Badawi Macarena Gómez-Mármol Aida Maria Diez Sarabia Madalina Ciobanu Akira Morikawa Magdalena Gizowska Ákos Kuki Magdalena Zdanowicz Alejandro Medina Manju Khari Alex Fan Xu Maqsood Malik Alexander M. Volodin Marcia Regina Assalin Alexander Wittemann Marcin K. Wojs Alina Kowalczyk-Juśko Marco Vaccari Amitava Moulick Marcos F. S. Teixeira Amr Fouda Marek Ochowiak Ana Sofia Dias Mestre Maria Emilia Brassesco Ananthakumar Ramadoss Maria Portarapillo Andras Erdohelyi Maria Ricciardi Andrea Ragusa Maria Włodarczyk-makuła Andreas Jess Mariateresa Lettieri Andrew C. Chien Marica Muscetta Anna Fajdek-Bieda Marina G. Khmeleva Anna Wołowicz Marta Stucchi Anton Petukhov Martin Carlos Antonello Barresi Márton Szabados Antonije Onjia Marvin Ricaurte Antonio Gagliano Mauricio Patón Antonio Jose Exposito Mengmeng Zhang Artem Belousov Miguel Menéndez Aurelian Cristian Boscornea Mikhail A. Il’yushin Ayman Youssef Ming Jiang Aymen Assadi Minghui Liang Barbara Sacchi Minh Vien Le Bartłomiej Zieniuk Miroslav Variny Benedikt Hülsemann Mohamad Fakhrul Ridhwan Samsudin Benyoucef Abdelghani Mohammad A. Hasnat Biljana Abramović Monica Francesca Pucci Boubié Guel Moro Daniele Bruno Sena Da Fonseca Mousumi De Sarkar Carmen Zaharia Muhammad Syafiq Hazwan Ruslan Chandra Mouli R. Madhuranthakam Muhammad Tahir Chetna Mohabeer Murali Dama Chuanyu Sun Natalija Velić Cláudio Rocha ‪Natasa Nastic Codina Movileanu Neli Mintcheva Cristian Barca Nicolae Gica Cristian Simion Nikolay Rodkevich Daniel Mamais Norshahidatul Akmar Mohd Shohaimi Danilo Escobar-Avello Nouf Faisal Alharby Dattatraya Subhedar Olvier Aubry Davide Clematis Oussama Baaloudj Depei Zhang Palani Molaiyan Dirk Tischler Paola Sangiorgio Doina Humelnicu Patrick Lott Domenico Flagiello Paweł Grabowski Domingo Martín Payam Sarir Donato Fontanarosa Peng Du Dong Jin Yoo Peng Li Duong Nguyen Petar Varbanov Ece Polat Peter Lang Elena López-Maya Petr Šálek Elmar Villota Peyman Roudgar Saffari Emanuel M. Fernandes Pietro Ballone Emerson H. De Faria Polina Tyubaeva Emma Palo Pothiappan Vairaprakash Enrico Andreoli Preety Ahuja Ermelinda Falletta Przemyslaw Bartczak Esin Varol Qiang Chen Eva Oktavia Ningrum Qicheng Feng Federica Turrini Radek Šulc Felix Brück Rafik Saddik Fiderman Machuca-Martínez Rahul Kavthe Filipe Hobi Bordón Sosa Rajesh Haldhar Filippo Samperi Ramona Kuhn Ghanshyam Singh Chauhan Reda Elkacmi Ghulam Ali Rika Ochi Godvin Sharmila V. Rodrigo Sávio Pessoa Gospodinka Gicheva Rosalinda Inguanta Govindasamy Mani Sanjeev Kumar Ujjain Granch Berhe Tseghai Savelii Kukharets Grażyna Wejnerowska Sayan Banerjee Guixia Zhao Shahabaldin Rezania Guoqin Huang Shuai Qian Hak Joo Kim Shuai Wang Hamid Eisazadeh Silvia Vasiliu Hangfeng Zhang Simone Rossi Hasi Rani Barai Sinan Kutluay Heitor Bento Sivasankar Annamalai Hongfei Ma Sonal V. Bhujbal Hugo A. L. Filipe Srikanth Vuppala Hugo Rojas-Chávez Sriram Ganesan Igor M. Piskarev Stefan Jopp Igor Prikhodko Stefan Krakowiak Igor Schreiber Supriya Chavan Ionuț Banu Susan E. Henkelis Iqrash Shafiq Sylwester Furmaniak Irene Samy Fahim Szabolcs Muráth Irene Tagliaro Thais Milessi Islam Md. Aminul Thanh Tin Nguyen Ivalina Avramova Thomas Waluga Jacek Andrzejewski Timothy Hunter Jakub Mokrzycki Tomasz A. Prokop Jayanthi Kumar Ufuk Malayoglu Jenshinn Lin Valerio Paolini Jin Niu Vamsee Vadlamudi Jinbo Fei Vasile Lavric Joanna Piotrowska-Woroniak Vikram Uttam Pandit Jorg Thöming Vincenzo A. Riggio Jorge L. Folch-Mallol Wei Luo Joshua Van Der Zalm Wenjia Wang Józef Haponiuk Weon Bae Ko Junghwan Kim Wojciech Janczukowicz Kai Wang Xiaojun Liu Katarzyna Cieślak Xin Gao Kingo Ariyoshi Xinquan Cheng Kirill M. Skupov Yifeng Tian Kondo-Francois Aguey-Zinsou Yong Ren Krzysztof Formela Yu-Chun Chiang Krzysztof Kruczala Yueping Wang Kumarasamy Sudhakar Yung-Ching Ding Ladislav Lukáč Yunxiang Xie Lahoucine Bahsis Yuxi Xie Lalit R Kumar Zaida Ortega Lei Li Zengqian Shi Leszek Kadziński Zheng Zhou Liangjun Xia Zhigang Zang Liliana Lazar Zhong-Ning Xu Lorenzo Guazzelli Zhuolin Ye Louis Wy Liu Zupeng Chen Luciano C. Almeida Footnotes Disclaimer/Publisher’s Note: The statements, opinions and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s). MDPI and/or the editor(s) disclaim responsibility for any injury to people or property resulting from any ideas, methods, instructions or products referred to in the content.